Nutrients and liming requirements on the bean dry matter production in a Yellow-Red Latosol in the Barretos region, São Paulo State - Caballero, Segundo Urquiaga; Stefanelli, Daniel; Oliveira, Clarice de; Vidal, Rael (Pesquisa Agropecuaria Brasileira, 2014)
This research was developed in greenhouse using samples of the surface layer (0-20 cm) of a Yellow-Red Latosol, sandy phase, profile from Barretos, São Paulo State, Brazil. The objective was to determinate the nutrient needs to be supplied to optimize the bean (Phaseolus bulgaris, L.) productivity on a representative soil of this region. The crop grew in pots with 2.0 kg of soil, fertilized with N, NP, NPK, NPKS, NPK plus micronutrients and without fertilizer. The nutrient levels applied were 100 ppm (mg. kg-1) of N, P and K, 135 mg S/kg of soil and 1, 2, 0-5 and 5 ppm of B, Cu, Mo and Zn, respectively. The soil samples of all these treatments received 2 mEq CaCO3/100 g. One treatment with N, P and K, without liming, was studied too. The dry matter yield of the branches + leaves, roots, pods and grains have been evaluated. Results indicated that: 1) the phosphorus increased significantly the yield of all bean-plant parts as much as duplication of grain yield; 2) the treatment with N, P, K, liming and micronutrients produced the highest yield of all bean-plants parts as much as quadruplication of grain yield; 3) the amount of potassium and calcium to treatments with NP and NPK, respectively, increased the pod and grain yield, without affecting the vegetative growing of the plant; 4) the higher grain yield wasn’t associated with highest vegetative growing.